Implementasi Skrining DASS-42 dan Edukasi Kesehatan Mental Sebagai Upaya Promotif dan Preventif Pada Mahasiswa Keperawatan - Tiffatul Jannah Firdausya; Fitri Annisa; Shierly Ramadhani; Diyah Putri Latifa (Community Service Articles, 2026)
Mental health issues among college students are a crucial issue, particularly during the academic transition phase, which is characterized by increased learning demands and psychosocial adaptation. This Community Service (PkM) activity aims to raise mental health awareness and conduct early detection of stress, anxiety, and depression risks among second-year students in the third and fourth semesters through workshops and mental health risk screening outreach. The activity methods included interactive mental health education and screening using the DASS-42 instrument. Students actively participated in all activities. Results showed that although the majority of students were in the normal to mild category, there were still students with moderate to severe levels of stress, anxiety, and depression, indicating a group of at-risk students. Furthermore, this activity contributed to increased student understanding and awareness of the importance of maintaining mental health and encouraged openness to seeking help. It can be concluded that the workshop and mental health screening outreach are effective promotive and preventive strategies in higher education environments and need to be continuously integrated with campus counseling services to support student psychological well-being.